Evaluación técnica de los métodos de obtención de abono a partir de excretas bovinas en la finca el Mirador De Las Marías, Guaduas (2021)
This work was carried out with the purpose of finding a method for the production of manure from bovine excreta generated during the fattening process in the production of cattle for slaughter and consumption at the Mirador de las Marías farm located in the Aguas claras district of Guaduas. Initially, a bibliographic review was carried out to identify the methods of manure production, biodigestion and composting, with their different operation mechanisms. Then, a characterization of the current disposal process was carried out, identifying which production method is used and analyzing the physicochemical characteristics of the raw material and the finished product.